Bond order via light-induced synthetic many-body interactions of ultracold atoms in optical lattices - Caballero-Benitez, S; Mekhov, I (IOP Publishing, 2016)
We show how bond order emerges due to light mediated synthetic interactions in ultracold atoms in optical lattices in an optical cavity. This is a consequence of the competition between both short- and long-range interactions designed by choosing the optical geometry. Light induces effective many-body interactions that modify the landscape of quantum phases supported by the typical Bose–Hubbard model. Using exact diagonalization of small system sizes in one-dimension, we present the many-body quantum phases the system can support via the interplay between the density and bond (or matter–wave coherence) interactions. We find numerical evidence to support that dimer phases due to bond order are analogous to valence bond states. Different possibilities of light-induced atomic interactions are considered that go beyond the typical atomic system with dipolar and other intrinsic interactions. This will broaden the Hamiltonian toolbox available for quantum simulation of condensed matter physics via atomic systems.